Pharmacokinetics of K117 and K127, two novel antidote candidates to treat Tabun poisoning - Tekes, K; Karvaly, G; Nurulain, S; Kuca, K; Musilek, K; Adeghate, E; Jung, Y-S; Kalász, H (Chemico-biological interactions, 2019)
AIMS: K117 and K127 are bis-pyridinium aldoximes but K117 is a bis-pyridinium bis-aldoxime while K127 has only one single aldoxime in addition to its amide substituent. Is there any difference in pharmacokinetics in these compounds that otherwise have the same chemical structure? Both K117 and K127 are developed as antidotes in acetylcholinesterase and butyrylcholinesterase poisoning in terrorist attacks or intoxication with other organophosphorous compounds. Their distributions have been scouted in the bodies of rats. MAIN METHODS: White male Wistar rats were intramuscularly injected. The animals were sacrificed, tissue samples were homogenized, and either K117 or K127 concentrations were determined using reversed-phase high-performance liquid chromatography. KEY FINDINGS: Both K117 and K127 were present in all tissues that were analyzed including blood (serum), the brains, cerebrospinal fluid, the eyes, livers, kidneys, lungs and testes. Their pharmacokinetics and body distributions are similar. SIGNIFICANCE: Either K117 or K127 meets the essential requirements for antidotes. Dose dependence and kinetics of their distribution were compared to that of other pyridinium aldoximes.
Keywords: Tissue Distribution; pyridinové sloučeniny; Rats; Acetylcholinesterase; Butyrylcholinesterase; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; butyrylcholinesterasa; Cholinesterase Inhibitors; Rats, Wistar; Distribution; Oximes; K117; krysa rodu Rattus; Pyridinium Compounds; organofosfáty; antidota; zvířata; tkáňová distribuce; chemické bojové látky; Organophosphates; K127; Antidotes; potkani Wistar; Chemical Warfare Agents; HPLC; Pyridinium aldoxime; oximy; reaktivátory cholinesterasy; Animals